History and Development of the Rewang Tradition in Rahuning Village, Asahan Regency, 2019–2025 - Aurindya, Alda; Nasution, Kasron (Medan Resource Center, 2026)
This study examines the historical background, development, and socio-cultural meanings of the rewang tradition in Rahuning Village, Asahan Regency, during the period 2019–2025. The research focuses on how this local tradition has adapted to social transformation and modernization while maintaining its communal values. Using a qualitative historical approach through interviews, observation, documentation, and literature study, this research explores the continuity and transformation of rewang within contemporary rural society. The findings reveal that rewang has historically functioned as a form of communal solidarity rooted in mutual assistance, kinship, and collective responsibility. During 2019–2025, the tradition experienced several shifts influenced by modernization, economic change, and evolving social interaction patterns, particularly in the organization and participation mechanisms of communal activities. Despite these transformations, the essential values of togetherness, cooperation, and social cohesion remain strongly preserved within the community. This study argues that the rewang tradition demonstrates cultural resilience by adapting to changing social conditions without losing its fundamental cultural identity, thereby reinforcing its continuing relevance in maintaining social harmony in Rahuning Village.